2019
DOI: 10.1016/j.crwh.2019.e00106
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro fertilization resulting in heterotopic pregnancy, ovarian hyperstimulation and paralytic ileus: A case report

Abstract: Heterotopic pregnancy followed by ovarian hyperstimulation syndrome and paralytic ileus are rare and potentially fatal complications associated with assisted reproduction. A 37-year-old nulliparous woman, after in-vitro fertilization and embryo transfer, presented to the gynaecology department with severe abdominal distension, diffuse abdominal pain and vaginal bleeding. Transvaginal ultrasound examination revealed an intrauterine pregnancy, with both ovaries enlarged, measuring 10cmx10cm, with free fluid in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nabi et al preferred TVUS compared to transabdominal ultrasound and suggested that if exams are inconclusive, high resolution TVUS or even magnetic resonance imaging (MRI) could be employed [11]. One might also consider taking into 160 consideration an elevated white blood cell (WBC), which was recorded in our case and several others, such as those described by Madžarac et al, who recorded a WBC of 31.8 × 10 9 /L, and Černiauskaitė et al, who described a WBC of 18.11 × 10 9 /L [6,12].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Nabi et al preferred TVUS compared to transabdominal ultrasound and suggested that if exams are inconclusive, high resolution TVUS or even magnetic resonance imaging (MRI) could be employed [11]. One might also consider taking into 160 consideration an elevated white blood cell (WBC), which was recorded in our case and several others, such as those described by Madžarac et al, who recorded a WBC of 31.8 × 10 9 /L, and Černiauskaitė et al, who described a WBC of 18.11 × 10 9 /L [6,12].…”
Section: Discussionmentioning
confidence: 73%
“…Letrozole, an aromatase inhibitor, works similarly by blocking the conversion of androgens into estrogen, which causes a subsequent increase in FSH, encouraging the growth and development of multiple follicles in the ovaries of women who are seeking fertility treatment [5]. Theoretically, since letrozole stimulates ovulation there is an increased risk of multiple gestation, and by default an increased risk of heterotopic pregnancy [6]. Interestingly, despite this theoretical risk, only one other case of heterotopic pregnancy has been documented in a patient with letrozole augmentation, making this a noteworthy exhibition [7].…”
Section: Introductionmentioning
confidence: 99%